Hubungan Tingkat Harga Diri dengan Gaya Hidup Konsumtif Remaja - Zuliani Zuliani; Athi’ Linda Yani; Arifa Retnowuni; Anna Qomariana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research is entitled "The Relationship between Self Esteem Level and Consumptive Lifestyle of High School Teenagers in Dormitory X Hurun Inn Pondok Pesantren Darul 'Ulum Peterongan, Jombang Regency". The purpose  this study was to understand how the level of self-esteem of adolescents relates to their consumptive lifestyle. In this study, researchers used a quantitative method with a cross-sectional approach, involving 58 teenagers living in a dormitory. Respondents were randomly selected using simple random sampling technique. The results showed that almost half of the respondents had a high consumptive lifestyle, while a small proportion had a low and moderate consumptive lifestyle. Hypothesis testing conducted using the Spearman rho method showed a value of P = 0.04, which means there is a significant relationship between low self-esteem and a high consumptive lifestyle among adolescents. From these results, it can be concluded that it is important to conduct interventions that can improve adolescents' self-esteem, taking into account the consumptive lifestyle they lead. This study is expected to provide insights for the development of better programs for adolescents in the pesantren environment.